Identification of the optimal treatment strategy for complex appendicitis in the paediatric population: a protocol for a multicentre prospective cohort study (CAPP study). Issue 2 (17th February 2022) - van Amstel, Paul; Bakx, Roel; van der Lee, Johanna H; van der Weide, Marijke C; Eekelen, Rik van; Derikx, Joep P M; van Heurn, Ernest L W; Gorter, Ramon R
Abstract : Introduction: In daily practice large heterogeneity in the treatment of children with complex appendicitis exists. Complex appendicitis can be divided into two subtypes; complex appendicitis with and without appendiceal mass and/or abscess. As complex appendicitis is associated with high morbidity and costs, identification of the optimal treatment strategy is essential. In this article, we present the study protocol for the CAPP (Complex Appendicitis in the Pediatric Population) study. Methods and analysis: This nation-wide, multi-centre, comparative, non-randomised prospective cohort study includes all children <18 years old with a preoperative suspicion of complex appendicitis, which is based on imaging confirmed acute appendicitis and predefined criteria regarding the severity of appendicitis. Eligible patients are recruited in more than 30 hospitals. Open appendectomy will be compared with laparoscopic appendectomy for children without appendiceal mass and/or abscess and initial non-operative treatment (ie, intravenous antibiotics with or without percutaneous drainage) to direct appendectomy for children with appendiceal mass and/or abscess. Based on historical data supplied by the participating hospitals and an inclusion period of 2 years and 9 months, a sample size of 1308 patients is aimed. Primary outcome is the proportion of patients experiencing any complication at 3 months follow-up. Reported complications will be assessed by an independent adjudication committee. Secondary outcomes include, but are not limited to, quality of life, and (in)direct costs. To adjust for baseline differences and selection bias, outcomes will be compared after propensity score analysis (inverse probability weighting and stratification). Ethics and dissemination: The Medical Ethics Review Committee of the Amsterdam UMC, location AMC, declared that the Medical Research involving Human Subjects Act (WMO) did not apply to this study. Therefore, no official approval was required by national law. Study results will be presented in peer-reviewed scientific journals and at (inter)national conferences. Trial registration numbers: NCT04755179 ; NL9371.